Pembuatan Hand Sanitizer dari Limbah Sampah Organik Dalam Peningkatan Pendapatan Di Era Pandemi covid-19 Di Desa Kaliwungu, Kecamatan Jombang - Shinta Wurdiana Rhomadona; Herisa Dinarsih (Universitas Merdeka Surabaya, 2020)
The public view of waste generated from household or industrial activities is something that is no longer desirable or has no economic value. In fact, fruit and vegetable waste from households can be used to make eco-enzyme products. Eco-enzymes are complex organic substance solutions produced from the fermentation process of organic residues, sugar and water. Eco-enzymes can be used as a disinfectant and handsanitizer, while for health it can be used to relieve infections and allergies in children and heal wounds. In the Sanggar Hijau Indonesia waste bank, Kaliwungu Village, Jombang District, Jombang Regency, East Java, they have produced processed eco-enzyme waste but do not yet have high selling power and their use is only used by members of the group. So that the people around them only think that eco-enzym products do not have superior economic value or if they are sold the price is too cheap, even if the harvest is a lot they are often wasted because they have not been used optimally and no one wants to buy. Even though with just a simple touch of technology from the method of manufacture, packaging that is more attractive than just being packaged through ordinary used mineral bottles and proper marketing can be processed products that are of high value and multipurpose. Therefore, with this Community Partnership Program, partners, namely Sanggar Hijau Indonesia, can increase their capacity in optimizing the processing of eco-enzyme waste into handsanitaizer products and multipurpose products in training and mentoring activities on manufacturing, packaging and marketing so that it is expected to increase income from these activities and eco-enzyme waste is not sold at low prices or only becomes the personal consumption of members and can have an impact on a better community life and can be an example for villages around Sanggar Hijau Indonesia in increasing income while being able to support government programs, especially environmental and health sustainability in the Covid-19 pandemic.